Therapeutic Response In Mycetoma â€" A Study Of Different Regimens - Kaliswaran A V; Sentamilselvi G; Janaki C; Janaki V R (Wolters Kluwer Medknow Publications, 2003)
Treatment of mycetoma is always considered a challenge to the dermatologists. Hence this study was undertaken to determine the efficacy of various therapeutic regimens in actinomycotic and eumycotic mycetoma. A total of 25 patients including 18 cases of actinomycotic mycetoma and 7 cases of eumycotic mycetoma was included. Combinations of trimethoprim-sulfamethoxazole (TS) with rifampicin (regimen-3), and TS monotherapy (regimen-4) were used in 9,2,1 and 6 patients with actinomycotic mycetoma respectively. Ketoconazole (regimen-A) and itraconazole (regimen-B) were used in patients with eumycotic mycetoma along with surgical excision (in amenable cases). Remission was observed in 10 cases of actinomycotic mycetoma (eight with Welsh regimen) and one case of eumycetoma who was subjected to surgical excision followed by oral ketoconazole. Improvement was seen in 2 cases of actinomycetoma treated one each with Welsh regimen and regimen4: in 2 cases of eumycetoma treated with ketoconazole in one and itraconazole in the other. No significant adverse effect was noted in the study except ototoxicity and reaction to streptomycin in one patient. In general, therapeutic outcome was excellent in patients with actinomycotic mycetoma particularly with Welsh regimen, whereas the response to medical therapy in eumycetoma is not satisfactory. Complete surgical excision followed by antifungal therapy at an early stage for eumycotic mycetoma is perhaps the best possible therapeutic modality in the present scenario.